A bibliometric analysis of two decades of aromatherapy research. (December 2017) - Koo, Malcolm
Abstract Background Quantitative data are lacking on the profile of published research in aromatherapy. The objective of the study was to investigate the profile of original and review articles under the topic aromatherapy using bibliometric analysis. Methods Articles on aromatherapy, published between 1995 and 2014, were retrieved from the Science Citation Index-Expanded database from the Web of Science. The records extracted were analyzed for citation characteristics, including the distribution of publication years, languages, countries or regions, journals, articles, and authors using HistCite 12.03.17. VOSviewer v.1.61 was used to construct bibliometric diagrams. Results A total of 549 original and review articles, published in 287 different peer-reviewed journals by 1888 authors, were identified. There was a steady increase in the number of published articles from 1995 to 2014. The majority of the articles was written in English (95.8%) and the United States was the leading country in the total number of published articles (n = 107, 19.5%)Journal of Alternative and Complementary Medicine published the greatest number of articles on the topic (n = 31, 5.6%). The article that received the greatest number of citations was published inComplementary Therapies in Medicine. Visualization analysis based on co-occurrences of words in the title and abstract revealed three clusters of research topics, including essential oil, intervention, and complementary medicine. Conclusions This study provided a systematic overview of productivity and visibility of research work in aromatherapy and the findings could be used for organizing and prioritizing future research efforts in aromatherapy research.